The Impact of Teachers' Mastery of Information and Communication Technology on Student Learning Motivation During Pandemic - Qaulan Syadida; Honest Ummi Kaltsum (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study aimed to determine whether teachers' mastery of ICT influenced students' motivation to learn during this pandemic time. This study employs a quantitative research design with a correlational research design. The participants in this study were 30 fourth-grade students from SDN Karangasem 02 Surakarta. Because every member of the population was sampled, the sampling strategy used in this study was a saturated sampling strategy. A questionnaire was used to collect data on ICT mastery and learning motivation. The Product Moment Correlation is used to test the validity of each item statement, and Cronbach Alpha is used to test the reliability. The normality test employs the Liliefors method, the homogeneity test employs the Harley method, and the hypothesis test employs the t-test. The results of this study indicate that there is an influence of teachers' ICT mastery on students' learning motivation during the pandemic. The teacher's level of ICT mastery could have had a 38% impact on the motivation of students to learn during the pandemic. The findings of this study provide elementary school teachers and school administrators with information about the impact of teachers' ICT mastery in online learning during the pandemic on students' learning motivation.